Beware, an underdog may bite: literature review and brand management framework in the context of underdog brands - Holger J. Schmidt; Pieter Steenkamp (Journal of Brand Management, 2021)
An underdog brand is a brand with humble resources that competes with passion and determination against competitors that dominate a market. Numerous anecdotal examples and a few research articles of underdog brands exist, yet the understanding of what an underdog brand is and how brands can use the underdog effect is still limited. Considering the relevance of underdog brand management for practice, the purpose of our article is to distill the components of the concepts "underdog brand" and "the underdog effect" and to propose a conceptual framework to guide underdog brand management. To achieve this goal, we undertook a systematic review of the extant literature that resulted in (1) a clear and demarking definition of the term underdog brand, (2) an analysis of the usefulness of the underdog effect and (3) a reference frame we termed "the underdog brand management framework". By doing so, we helped to overcome the research gap in the field of underdog brand management. To validate our findings, we tested the framework against a case study of a successful underdog brand. Our analysis resulted in a robust model that could inspire and guide practitioners who are in charge of underdog brands.
Keywords: 330; Underdog brand; Underdog effect; Brand management; Brand biography; Literature review; Case study research